2015
DOI: 10.11648/j.sjph.20150301.19
|View full text |Cite
|
Sign up to set email alerts
|

Unwanted Pregnancy and Associated Factors among Female Students of Madawalabu University Bale Zone, Oromia Region South East, Ethiopia

Abstract: Abstract:Globally as well as in the developing world unintended pregnancies are among the major social and health problems. In Ethiopia, 54% of pregnancies to girls under age 15 are unwanted. In some countries where accesses to safe and legal abortion services are restricted, unsafe abortion is the cause for more than 30% of maternal deaths. The aim of this study was to assess factors associated with unwanted pregnancy among female students of Madawalabu University from 01-21, March 2014. A cross sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…8 In Wolaita Sodo university, southern Ethiopia, a rate of 32.4% unintended pregnancy was found. 9 One of the key strategies to prevent these problems is the availability and utilization of contraceptives. 10 Countries in the world designed and used different strategies to effectively enhance the utilization of sexual and reproductive health services like contraceptives.…”
Section: Introductionmentioning
confidence: 99%
“…8 In Wolaita Sodo university, southern Ethiopia, a rate of 32.4% unintended pregnancy was found. 9 One of the key strategies to prevent these problems is the availability and utilization of contraceptives. 10 Countries in the world designed and used different strategies to effectively enhance the utilization of sexual and reproductive health services like contraceptives.…”
Section: Introductionmentioning
confidence: 99%
“…The sociodemographic features of the respondents are such as the mean age of the students is 22.1 with the range of 18-26.1; single female students were predominant with 94% while the field of medical techniques alone accounted for 45%. According to research done in many university institutions, the mean age of female students is around 20 years old [18], [19].…”
Section: Discussionmentioning
confidence: 99%
“…The enormous consequences linked to this active sexuality have been noted in most universities: for example, unwanted pregnancies, (18), resulting from the non-use of contraceptives as condoms by feeling embarrassed or ashamed to use or purchase condom/contraceptives" [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study conducted in one of Ethiopian university (Mada Wolabu University) showed that prevalence of unintended pregnancy was about 32.4% [14].…”
Section: Introductionmentioning
confidence: 99%